2013
DOI: 10.1371/journal.pone.0055910
|View full text |Cite
|
Sign up to set email alerts
|

Integrated MicroRNA and mRNA Signatures Associated with Survival in Triple Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous disease at the molecular, pathologic and clinical levels. To stratify TNBCs, we determined microRNA (miRNA) expression profiles, as well as expression profiles of a cancer-focused mRNA panel, in tumor, adjacent non-tumor (normal) and lymph node metastatic lesion (mets) tissues, from 173 women with TNBCs; we linked specific miRNA signatures to patient survival and used miRNA/mRNA anti-correlations to identify clinically and genetically different TNBC subcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
151
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 49 publications
10
151
2
3
Order By: Relevance
“…however, miR-493, as analyzed by NanoString's nCounter human miRNA expression profiling, was downregulated in TNBCs vs. normal breast tissues (37). The role of miR-493-5p remains unclear in breast cancer cell lines and in breast cancer at present.…”
Section: Discussionmentioning
confidence: 97%
“…however, miR-493, as analyzed by NanoString's nCounter human miRNA expression profiling, was downregulated in TNBCs vs. normal breast tissues (37). The role of miR-493-5p remains unclear in breast cancer cell lines and in breast cancer at present.…”
Section: Discussionmentioning
confidence: 97%
“…Very recently, Cascione et al determined miRNA expression profiles to stratify TNBCs and identified miRNA signatures that correlated with prognosis and were independent predictors for OS and DFI (36 ). Radojicic et al recently explored the expression profile of miRNAs in TNBC and reported that there was a nonsignificant trend for high expression levels of the miRNAs miR-21, miR-210, miR-221, and miR-222 to be associated with worse patient DFI and OS (37 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a highly conserved group of short noncoding RNAs ($22 bp) that play a major role in posttranslational regulation of gene expression and are critical regulators of oncogenic pathways (5). miRNAs have been widely associated with breast cancer tumorigenesis (6), as well as with prognosis and response to treatment in breast cancer (7,8). A recent study by Dvinge and colleagues (9) describes the landscape of miRNA expression in 1,302 primary breast tumors accompanied by matched clinical information and genomic and transcriptomic data (10).…”
Section: Introductionmentioning
confidence: 99%